Combined effects of heatwaves and micropollutants on freshwater ecosystems: Towards an integrated assessment of extreme events in multiple stressors research. (16th November 2021) - Polazzo, Francesco; Roth, Sabrina K.; Hermann, Markus; Mangold‐Döring, Annika; Rico, Andreu; Sobek, Anna; Van den Brink, Paul J.; Jackson, Michelle C.
Abstract: Freshwater ecosystems are strongly influenced by weather extremes such as heatwaves (HWs), which are predicted to increase in frequency and magnitude in the future. In addition to these climate extremes, the freshwater realm is impacted by the exposure to various classes of chemicals emitted by anthropogenic activities. Currently, there is limited knowledge on how the combined exposure to HWs and chemicals affects the structure and functioning of freshwater ecosystems. Here, we review the available literature describing the single and combined effects of HWs and chemicals on different levels of biological organization, to obtain a holistic view of their potential interactive effects. We only found a few studies (13 out of the 61 studies included in this review) that investigated the biological effects of HWs in combination with chemical pollution. The reported interactive effects of HWs and chemicals varied largely not only within the different trophic levels but also depending on the studied endpoints for populations or individuals. Hence, owing also to the little number of studies available, no consistent interactive effects could be highlighted at any level of biological organization. Moreover, we found an imbalance towards single species and population experiments, with only five studies using a multitrophic approach. This results in a knowledge gap for relevant community and ecosystem level endpoints, which prevents the exploration of important indirect effects that can compromise food web stability. Moreover, this knowledge gap impairs the validity of chemical risk assessments and our ability to protect ecosystems. Finally, we highlight the urgency of integrating extreme events into multiple stressors studies and provide specific recommendations to guide further experimental research in this regard. Abstract : We reviewed the available literature describing the single and combined effects of heatwaves and chemicals on different levels of biological organization. We found that only few studies addressed these stressors in combination. Moreover, we highlight the imbalance towards single species and population experiments. This results in a knowledge gap for relevant community‐ and ecosystem‐level endpoints, which prevents the exploration of important indirect effects that can compromise food web stability. Finally, we highlight the urgency of integrating extreme events into multiple stressors studies and provide recommendations to guide further experimental research in this regard.